Recognition and Treatment of BCG Failure in Bladder Cancer - Andrew J. Lightfoot; Henry M. Rosevear; Michael A. O'Donnell (The Scientific World Journal)
Patients with high-grade Ta, T1, or carcinoma in situ non–muscle-invasive bladder cancer (NMIBC) are at high risk for recurrence and, more importantly, progression. Thus, both the American Urological Association and European Association of Urology recommend initial intravesical treatment with bacillus Calmette-Guerin(BCG) followed by maintenance therapy for a minimum of 1 year. The complete response rate to BCG therapy in patients with high-risk NMIBC can be as high as ∼80%; however, most patients with high-risk disease suffer from recurrence. BCG failure can be further characterized into BCG refractory, BCG resistant, BCG relapsing, and BCG intolerant. Current recommendations include one further course of BCG or cystectomy. In patients who continue to fail conservative treatment and who refuse surgical therapy or are not surgical candidates, treatment options become even more complicated. In this setting, treatment options are limited and include repeat BCG treatment, an alternate immunotherapy regimen, chemotherapy, or device-assisted therapy. To date, however, further research is necessary for all secondary treatment options in order to determine which might be the most efficacious. All conservative treatments should be considered investigational. Currently, cystectomy remains the standard of care for high-risk patients who have failed BCG therapy.